2018
DOI: 10.1038/s41598-018-22675-1
|View full text |Cite
|
Sign up to set email alerts
|

High-speed photon-counting laser ranging for broad range of distances

Abstract: We demonstrate a high-speed photon-counting laser ranging system with laser pulses of multiple repetition rates to extend the unambiguous range. In the experiment, the laser pulses of three different repetition rates around 10 MHz were employed to enlarge the maximum unambiguous range from 15 m to 165 km. Moreover, the range of distances was increased as well, enabling the measurement on different targets of large separation distance with high depth resolution. An outdoor photon-counting laser ranging up to 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 18 publications
0
31
0
1
Order By: Relevance
“…However, many relevant quantum systems, including trapped ions [12] and color centers in diamond [13], operate in the visible spectrum, which makes efficient, low-noise SPADs for visible wavelengths highly desirable. Such devices would also find numerous applications in other important technologies, including LIDAR [14], non-line-of-sight imaging [15], and fluorescence medical imaging [16].…”
mentioning
confidence: 99%
“…However, many relevant quantum systems, including trapped ions [12] and color centers in diamond [13], operate in the visible spectrum, which makes efficient, low-noise SPADs for visible wavelengths highly desirable. Such devices would also find numerous applications in other important technologies, including LIDAR [14], non-line-of-sight imaging [15], and fluorescence medical imaging [16].…”
mentioning
confidence: 99%
“…The problem becomes even more acute in the presence of fog, which is a major concern for the next generation of automated cars. It has been demonstrated that it is technically possible to detect and analyze fog patches over long distances, provided that the laser power is sufficient to ensure a nonzero probability of photon reflection and a long enough acquisition time (62,63). In the automotive context, where the acquisition time is intrinsically limited by the vehicle displacement velocity, more robust and computationally efficient strategies have been recently proposed (51,64), and it is clear that future imaging systems will incorporate computational models for both the propagation physics of the medium and physical properties of the detector.…”
Section: Enhanced Spad Arrays For Imaging In Scattering Mediamentioning
confidence: 99%
“…In other words, it is difficult to employ for long-range and high-speed moving target detection. Du [9] and Liang [10] demonstrated a high-speed photon-counting laser ranging system with laser pulses of multiple repetition rates to extend the unambiguous range. This is an effective method to realize long-range detection.…”
Section: Introductionmentioning
confidence: 99%